Evaluation of the Impact of the Youth Service: NEET programme - Sylvia Dixon; Sarah Crichton (New Zealand Government, The Treasury, 2016)
Youth Service: Not in Employment, Education or Training (or YS: NEET) is a government programme designed to encourage and assist disadvantaged 16-17 year olds to stay in education or training and improve their qualification attainment. Community organisations are contracted to undertake needs assessments and provide mentoring and support for these youth. This paper evaluates the impact of the programme on the educational retention, qualification achievement, benefit receipt, inactivity and employment rates of participating youth in the 18-24 months after they enrol in YS: NEET. Administrative data from the Integrated Data Infrastructure (IDI) is used to measure individuals' outcomes. The impacts of the programme are estimated by comparing the outcomes of participants with those of a matched comparison group of similar youth who did not participate.
Keywords: I38; 330; Youth transitions; youth mentoring; not in employment; education or training; impact evaluation; Jugendarbeitslosigkeit; Weiterbildung; Arbeitsvermittlung; Arbeitsmarktintegration; Beschäftigungseffekt; Junge Arbeitskräfte; Neuseeland